Pencapaian SIG: SERG / Ts. Dr. Mohd Zaki Mohd Yusoff - Mohd Yusoff, Mohd Zaki (Jabatan Sains Gunaan, 2021)
*Sensor and Environmental Research Group (SERG) *Research on Semiconductor Materials, Device and : Applications. Nanomaterials. Analytical Chemistry and Supramolecular Chemistry *Background of members *Fellows *Pencapaian SERG (2020) *Lain -lain pencapaian SERG (2020)